Culturally Mixed Group Work and the Development of Students' Intercultural Competence. (February 2022) - Liang, Yuwei; Schartner, Alina
Culturally mixed group work has become a common mode of assessment in higher education to encourage students from different cultural and linguistic backgrounds to learn from and work with each other. This article aims to address whether culturally mixed group work can contribute to students' intercultural competence (IC) development. The Multicultural Personality Questionnaire was used to measure students' IC development over time, while three waves of interviews investigated students' attitudes on culturally mixed group work. Findings suggest that both staff and students think culturally mixed group work can be beneficial and is an effective way to develop IC and increase intercultural awareness. However, students perceived it as both rewarding and challenging. Findings showed that without staff guidance, mixed group activities can cause a long-term negative effect on students' open-mindedness. This result points to a need to reconsider how mixed-culture group work can be utilized effectively in class.